Identifying the bottlenecks limiting medium-chain fatty acid accumulation in transgenic pennycress seeds - Alisha, Fnu (My University, 2025)
Pennycress (Thlaspi arvense) is an emerging oilseed biofuel crop within the Brassicaceae family, closely related to Arabidopsis thaliana. It holds significant potential as a platform for the production of biotechnologically derived compounds, such as medium-chain fatty acids. These are saturated hydrocarbon chain molecules with 8 to 14 carbon atoms. These are abundant in plants like coconut and species of Cuphea, including Cuphea viscosissima and Cuphea var. avigera pulcherrima, which can comprise up to 94 mol percent of the oil content. To enhance medium chain production, pennycress was genetically engineered to express a medium chain specific thioesterase and two MCFA-specific acyltransferases, resulting in the accumulation of carbon 10 chain fatty acids at 7 mol percent. Using systems biology approaches, this study aims to identify the bottlenecks in carbon 10 chain production in transgenic pennycress. Fatty acid composition analysis reveals increased levels of carbon 16 chain fatty acids in transgenic plants compared to wild-type plants, with a higher total fatty acid content throughout seed development. Lipidomic analysis reveals the production of altered carbon-10-containing triacylglycerols and acyl-sterol glucosides in transgenic plants, particularly during the later stages of seed development. Moreover, the levels of triacylglycerol containing multiple medium-chain fatty acids decline as seed development progresses. Transcriptomic analysis shows no significant changes in gene expression for most genes associated with fatty acid and triacylglycerol synthesis, degradation, and peroxisomal beta oxidation pathways. Notably, transcriptomic data also highlight several upregulated genes in transgenic seeds related to stress responses, including heat shock proteins and genes associated with hypoxia response.
Keywords: Pennycress; Medium chain fatty acids; Systems biology; Oilseeds